2017
DOI: 10.1016/j.jisp.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in Dermatology Residency Programs

Abstract: Given the change in our population to one that is more racially and ethnically diverse, the topic of diversity in dermatology residency programs has gained attention. In a field that has become highly competitive, diversity is lagging behind. What are the reasons for this? The existing diversity among medical school matriculants is reflective of the applicant pool, and although modest, there has been an increase in applications and acceptances from minority populations. However, these proportions do not carry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…In the last decade it has become increasingly apparent that the US population is diversifying and that patients with skin of color will comprise a substantial proportion of the future population, 8,11 which emphasizes the need for dermatology residency programs to ensure that residents receive adequate training and exposure to patients with skin of color as well as the distinct skin diseases seen more commonly in these populations. 12…”
Section: Resultsmentioning
confidence: 99%
“…In the last decade it has become increasingly apparent that the US population is diversifying and that patients with skin of color will comprise a substantial proportion of the future population, 8,11 which emphasizes the need for dermatology residency programs to ensure that residents receive adequate training and exposure to patients with skin of color as well as the distinct skin diseases seen more commonly in these populations. 12…”
Section: Resultsmentioning
confidence: 99%
“…36 Furthermore, representation of UIM physicians practicing in academic settings, including pathologists, is declining. 32 Physicians who identify as UIM, and specifically black/African American and Hispanic/Latinx physicians, comprise only approximately 4% (approximately 40 500 and 43 700 of approximately 956 500 physicians, respectively) of the US physician workforce 37,38 despite comprising approximately 13% and 18% of the US population (43 984 096 and 60 724 311 of 328 239 523 people), respectively. 39 The limited pool of potential UIM applicants and lack of diversity among practicing pathologists further strain the recruitment of a diverse trainee population in pathology.…”
Section: Challenges In Trainee Recruitment To the Field Of Pathologymentioning
confidence: 99%
“…1 It is projected that by 2050 more than half of all Americans will belong to a minority group. 2 Minority patients have been shown to be more likely to have difficult physician-patient relationships, feel disrespected by the health care system, and experience barriers in obtaining health care. 1 Unfortunately, the same racial and ethnic minority groups that have poorer health status are also the most underrepresented in health professions.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 For example, according to the American Association of Medical Colleges, only 4.4% of physicians identify themselves as being of Hispanic or Latino ancestry, and 4.1% identify themselves as being of African American ancestry. 2 Deville and colleagues 8 demonstrated that these percentages are similar in graduate medical education (GME).…”
Section: Introductionmentioning
confidence: 99%